Batasan Rumah Susun yang Dijadikan Agunan pada Bank - Rizal Bahrudin (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
This paper aims to determine the existence and strength of executives certificate of liability to the property rights of apartment units as a guarantee of debt in credit agreements in the bank. The legal basis for the execution of encumbrance over apartment units is provided in Article 20 of the IRA (the Insurance Rights Act). The object of encumbrance is sold through a public tender in the manner prescribed in the prevailing laws and regulations. The holders of the encumbrance entitlements are entitled to take all or part of the proceeds for the repayment of the receivables, with the right that precedes it from the other creditor. The result shows that banks will not dare to provide loans or credit to the community without any guarantee. The ownership rights of apartment units can be used as the object of credit guarantee and tied with mortgage rights.